MANAJEMEN KASUS BAGI ORANG DENGAN HIV/AIDS (ODHA) DI RUMAH PERLINDUNGAN SOSIAL PHALAMARTHA SUKABUMI - Ellya Susilawati (Politeknik Kesejahteraan Sosial Bandung, 2012)
AbstractCase management is one method of intervention by Social Workers which intended is to provide a comprehensive service in addressing the needs and concerns of People Living with HIV-related medical and psychosocial problems. This study aims to notice at how the implementation of case management for People Living with HIV in the Rumah Perlindungan Sosial (Social House of Protection) of Phala Martha. The results of qualitative research with evaluation techniques conducted by Social Workers, Companions, Nurses and Case Managers indicated that RPS Phala Martha has implemented the elements of case management practices, but not as the case management stage yet. Aspects of case management practices which are implemented include: 1) A comprehensive assessment of client’s personal, health and problems associated with HIV / AIDS. Implementation of assessment conducted by Assessment Team consisting of Social Workers, Medical Teams and Counselors from the HIV/ AIDS NGO, 2) Make a plan for each client of PLHA through a case conference primarily concerned with medical intervention, however, individual care plan has not been fully written in every client’s file, 3) Providing information about services needed by PLHA is still limited, so the People Living with HIV are tend to seek information by themselves via internet. But, RPS has undertaken referrals for medical and social support for PLHA, 4) Provision of education and counseling services related with HIV / AIDS has been given by the counselor, 5) Advocacy activity has not been performed, 6) Medical care for PLHA consistenly done by nurses and doctors who served in RPS of PLHA Phala Martha. To enhance the case management strategies for People Living with HIV according to the stages of social work, the RPS Phala Martha should: 1) Reformulate the program of case management program as an unite program consist of aspects of case management in dealing with HIV / AIDS including assessment, planning, intervention, provision of information, provision of education and counseling, advocacy and consistency to medical care for all People Living with HIV, 2) Establish Social Worker as Case Manajer while the Medical Team, Counselor and Companion become partners in the process of care and treatment of PLHA; 3) Conduct regular reviews of service involving PLHA clients and families, and 4) Increase the capacity of social workers either in independent way or participate in the case managers trainings of PLHA in NGOs which have been engaged in HIV / AIDS field.Keywords: case management, PLHA, social worker, RPS Phala Martha AbstrakManajemen kasus merupakan salah satu metode intervensi yang dilakukan oleh pekerja sosial ditujukan untuk memberikan pelayanan yang komprehensif dalam menangani kebutuhan dan permasalahan ODHA berkaitan dengan permasalahan medis dan psikososial. Penelitian ini bertujuan untuk melihat bagaimana pelaksanaan manajemen kasus bagi ODHA di Rumah Perlindungan Phala Martha Sukabumi.Hasil penelitian kualitatif dengan teknik evaluasi yang dilakukan kepada pekerja sosial, pendamping, perawat dan manajer kasus menunjukkan bahwa RPS Phala Martha telah melaksanakan unsur-unsur praktik manajemen kasus namun belum sebagai tahapan manajemen kasus. Aspek-aspek praktik manajemen kasus yang dilaksanakan meliputi: a) asesmen komprehensif tentang data diri, kesehatan dan permasalahan klien berkaitan dengan penularan HIV/AIDS. Pelaksanaan asesmen dilakukan oleh tim asesmen yang terdiri dari pekerja sosial, tim medis dan konselor dari LSM HIV/AIDS; 2) membuat perencanaan untuk setiap klien ODHA melalui case conference terutama berkaitan dengan intervensi medis, namun demikian individual care plan belum tertulis di setiap file klien secara lengkap: 3) Penyediaan informasi yang tentang pelayanan yang dibutuhkan ODHA masih terbatas, sehingga ODHA cenderung mencari informasi sendiri melalui internet. Namun demikian RPS telah melaksanakan rujukan untuk pelayanan medis dan dukungan sosial bagi ODHA.; 4) pemberian layanan edukasi dan konseling berkaitan dengan HIV/AIDS telah diberikan oleh konselor; 5) kegiatan advokasi belum dilakukan; 6) pelayanan medis untuk konsistensi perawatan ODHA yang dilakukan oleh perawat dan dokter yang bertugas di RPS Odha Phala Martha.Untuk meningkatkan strategi manajemen kasus bagi ODHA sesuai dengan tahapan pekerjaan sosial, sebaiknya pihak RPS Phala Martha: 1) memerumuskan kembali program manajemen kasus sebagai satu program yang terdiri dari aspek-aspek manajemen kasus dalam penanganan HIV/AIDS meliputi asesmen, perencanaan, intervensi, penyediaan informasi, pemberian edukasi dan konseling, advokasi dan konsistensi untuk perawatan medis bagi setiap ODHA; 2) menetapkan pekerja sosial sebagai manajer kasus sedangkan tim kesehatan, konselor dan pendamping menjadi mitra dalam proses pelayanan dan perawatan ODHA; 3) melakukan review pelayanan secara reguler dengan melibatkan klien ODHA dan keluarga; dan 4) meningkatkan kapasitas pekerja sosial baik secara mandiri maupun ikut serta pelatihan manajer kasus ODHA di LSM yang telah bergerak dalam penanganan HIV/ADS.